Cutaneous larva migrans – case report and literature review - Ryguła, Anna; Kowalski, Michał; Hryncewicz-Gwóźdź, Anita; Maj, Joanna; Jankowska-Konsur, Alina (Family Medicine & Primary Care Review, 2023)
Cutaneous larva migrans (CLM) is a parasite dermatosis caused by skin penetration and the migration of larvae of the nematodes. The etiological factors are Ancylostoma braziliense and Ancylostoma caninum. The infection most often appears in tropical and subtropical countries. The main symptoms are creeping eruption, which is slightly elevated, migrating, erythematous and serpiginous track and severe pruritus. The areas that are the most occupied are the feet and buttocks. The diagnosis is based on characteristic clinical presentation and a history of tropical travel. The most frequently implemented treatment is ivermectin and albendazole. Ivermectin is used orally, 200 mcg/kg once daily for 1–2 days. Oral albendazole 400 mg once daily orally for 3 days is also a satisfying therapeutic option. There have also been reports of topical treatment with 10% thiabendazole cream or 1% ivermectin cream. Antihistamines can be helpful for the management of pruritus. Prevention of CLM includes wearing footwear at the beach and plays an extremely important role.